Cardiac rehabilitation in pediatric cardiomyopathy. (June 2018) - Thrush, Philip T.; Vogel, Casey
Abstract: Pediatric cardiomyopathies affect a small portion of the pediatric population, but the constellation of disorders encompasses a wide range of symptoms and disease severity. Medical and surgical therapies have continued to advance, and combined with increasing data from adult studies, cardiac rehabilitation likely has an important role in the care of these children as data shows benefits ranging from improved endothelial function to improved quality of life. While there are limited guidelines for exercise training and sports participation in children with cardiomyopathy, data to shape these guidelines remains sparse and the cardiomyopathy community is dependent upon expert opinions. Cardiac rehabilitation has been shown to be both feasible and safe although the studies are small and predominantly based on inpatient subjects with dilated cardiomyopathy which limits the applicability to other forms of cardiomyopathy and outpatient programs. Finally, multiple limitations exist to studying this area, but they are not insurmountable, and the evolution of technology may allow for innovative use of wearable technology to overcome some of these limitations. Highlights: Pediatric cardiomyopathies are rare but have a wide range of disease severity. There is limited data to guide both exercise and cardiac rehab in these pediatric patients. Cardiac rehabilitation has been showed to be feasible and safe in very small case series. Evolving wearable technology may help facilitate home rehabilitation in these children.